The evaluation of nurse navigators in chronic and complex care. (10th June 2019) - Harvey, Clare; Palmer, Janine; Hegney, Desley; Willis, Eileen; Baldwin, Adele; Rees, Clare; Heritage, Brody; Thompson, Shona; Forrest, Rachel; O'Donnell, Christopher; Marshall, Robert; Mclellan, Sandy; et al.
Abstract: Aim: With increasing age and chronicity in populations, the need to reduce the costs of care while enhancing quality and hospital avoidance, is important. Nurse‐led co‐ordination is one such model of care that supports this approach. The aim of this research was to assess the impact that newly appointed Navigators have on service provision; social and economic impact; nurses' professional quality of life and compassion fatigue; and analysis of the change that has occurred to models of care and service delivery. Design: A concurrent mixed‐method approach was selected to address the research aims. Methods: The research project was funded in July 2018 and will conclude in December 2020. Several cohorts will be studied including; patients assigned to a navigator, patients not assigned to a navigator, family members of patients assigned a navigator; and a sample sized estimated at 140 navigators. Discussion: This study provides a comprehensive international longitudinal and mixed method framework for evaluating the impact of nurse navigators on quality of care outcomes for patients with chronic conditions. Impact—What problem will the study address?: Even with specialty focused co‐ordinated care, patients get lost in the system, increasing the incidence of non‐compliance and exacerbation of condition. Navigators work with patients across service boundaries allowing for care that is patient responsive, and permitting variables in clinical, social and practical elements of care to be addressed in a timely manner. This novel nurse‐led approach, supports hospital avoidance and patient self‐management, while encouraging expansion and opportunity for the nursing and midwifery workforce. Abstract : 目的: 随着人口年龄和慢性化的增加, 在提高质量和避免住院的同时降低护理成本的需求显得非常重要。护士引导型协调就是支持这种方法的护理模式之一。这项研究目的在于评估新任导航员对服务提供的影响;社会和经济影响;护士职业生活质量与同情心疲乏;以及对护理和服务提供模式所发生变化的分析。 设计: 选择了并行混合方法来解决研究目标。 方法: 研究项目于2018年7月获得资助, 将于2020年12月结束。将研究几个队列, 包括:分配给导航员的患者、未分配给导航员的患者、分配给导航员的患者家属;和估计为140个航海家的样本量。 讨论: 本研究为评估护士导航员对慢性病患者护理结果质量的影响提供了一个全面型国际纵向和混合方法框架。 影响—— 研究将解决什么问题?以下内容: 即使有了专业专注型协调护理, 患者也会迷失在身体系统中, 从而增加不遵从和病情恶化的发生率。导航员跨越服务边界与患者合作, 考虑患者响应型护理, 并允许及时处理临床、社会和实际护理要素中的变量。这种新颖的护士主导型方法有助于避免住院和患者自我管理, 同时鼓励护理和助产人员的壮大和机遇。